MOTIVASI SEBAGAI FAKTOR PENINGKATAN KINERJA KEPOLISIAN - Sarida Sirait (Politeknik Bisnis Indonesia, 2019)
The National Police of the Republic of Indonesia is a civil servant in the Indonesian National Police. The National Police of the Republic of Indonesia aims to realize internal security which includes the maintenance of public security and order; orderly and upholding the law; the implementation of protection, protection and community service. This type of research is quantitative research with data collection techniques is a questionnaire. The questionnaire was distributed to all research samples, namely members of the Pematangsiantar police station. The results of this study are that there is a positive and significant influence between the motivation towards the performance discipline of the police in Pematangsiantar police station. With a significance level of 0.000, Motivation has a relationship of 58.3% of police performance seen from the percentage coefficient of determination, 41.7% affect other factors not examined.